PERANCANGAN MODUL PEMBELAJARAN HURUF BRAILLE BERBASIS MIKROKONTROLER UNTUK MEMBANTU PROSES BELAJAR DISABILITAS NETRA - Padma Diana, I Putu Agus; Putu Raka Agung, I Gusti Agung; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
We design Braille-learning module based on microcontroller as a helping tool for Braille-learning process for people with vision disabillity. The main operating system used is Arduino ATMega 2560 as the input data processor and provide output commands according to planning. The result is a system consists of a push-button Keyboard for data input, DFPlayer mini for sound output and a LCD for character display. Braille-learning module can be used for 5.6 hours under standby keyboard module condtion and 5.04 hours in keyboard module condition suppressed with minimum or maximum mini DFPlayer volume.